2018
DOI: 10.18632/oncotarget.25497
|View full text |Cite|
|
Sign up to set email alerts
|

The Nrf2 inhibitor brusatol is a potent antitumour agent in an orthotopic mouse model of colorectal cancer

Abstract: Nrf2 is a transcription factor that regulates cellular stress response and irinotecan-metabolising pathways. Its aberrant activity has been reported in a number of cancers, although relatively few studies have explored a role for Nrf2 in colorectal cancer (CRC). This study assessed the expression of Nrf2 in patient CRC tissues and explored the effect of Nrf2 modulation alone, or in combination with irinotecan, in human (HCT116) and murine (CT26) cell lines in vitro and in an orthotopic syngeneic mouse model ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 43 publications
(52 reference statements)
2
29
0
1
Order By: Relevance
“…Similarly, a comprehensive antitumor effect of BR, through the inhibition of cell viability and the promotion of apoptosis caused by autophagy, was identified in hepatocellular carcinoma . Furthermore, many previous studies have shown that BR functions as a tumor suppressor through the involvement of the Nrf2/HO‐1 pathway . In the present study, BR regulated the Nrf2/HO‐1 pathway to inhibit neurotoxicity in U‐251 cells.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, a comprehensive antitumor effect of BR, through the inhibition of cell viability and the promotion of apoptosis caused by autophagy, was identified in hepatocellular carcinoma . Furthermore, many previous studies have shown that BR functions as a tumor suppressor through the involvement of the Nrf2/HO‐1 pathway . In the present study, BR regulated the Nrf2/HO‐1 pathway to inhibit neurotoxicity in U‐251 cells.…”
Section: Discussionsupporting
confidence: 57%
“…In this regard, by using tissue microarrays, Evans and coworkers found that NRF2 was highly expressed in primary CRC and metastatic tissues compared to normal colon. Here, siRNAs against NRF2 or Brusatol were found to induce cell death in human (HCT116) and murine (CT26) cell lines, enhancing also the toxicity of Irinotecan, while Brusatol potently abrogated CRC tumor growth in subcutaneously and orthotopically allografted syngeneic mice [290] (see Table 1). In another very recent study, the cotreatment with Brusatol and UVA led to the inhibition of A375 melanoma cell proliferation triggering ROS-dependent apoptosis.…”
Section: Therapeutic Strategies For Nrf2 Inhibition In Cancermentioning
confidence: 99%
“…Other researchers took advantage of global repressors of protein synthesis such as brusatol or halofuginone to facilitate NRF2 degradation and prevent the refilling of its intracellular content at the post-transcriptional level in solid and hematologic tumors. By doing so, potent tumor suppressive effects and enhanced chemosensitivity largely derived by overwhelming ROS accumulation, were observed in pancreatic cancer cells [ 109 ], colorectal cancer cells [ 110 ], acute myeloid leukemia (AML) cells [ 111 ], and non-small cell lung cancer (NSCLC) cells [ 112 ]. Of note, halofuginone bromide is currently under phase-1 evaluation in a clinical trial conducted on patients with advanced solid tumors (NCT00027677).…”
Section: Nrf2 Modulators For Cancer Therapymentioning
confidence: 99%